Prospective associations of multidimensional well-being with work distraction and job satisfaction: a two-wave study of US employees - Fung, Eric N.; Cowden, Richard G.; Chen, Ying; Weziak-Bialowolska, Dorota; Bialowolski, Piotr; Lee, Matthew T.; McNeely, Eileen; VanderWeele, Tyler J. (Frontiers in Psychology, 2024)
Previous studies on the associations between well-being and work outcomes, such as work distraction and job satisfaction, have largely been cross-sectional and typically focused on only one or two aspects of well-being. Using two waves of data from a sample of employees at a United States health insurance company (n = 1,234), the present brief research report examines prospective associations between six domains of well-being (emotional health, physical health, meaning & purpose, character strengths, social connectedness, and financial security) and two work outcomes (work distraction and job satisfaction). Lagged regression analyses provided some evidence indicating that higher-level well-being in several domains was associated with subsequent reduced work distraction and increased job satisfaction assessed approximately one year later, but the magnitude of associations with each outcome did vary by specific domain. Emotional health and social connectedness were most strongly associated with work distraction and job satisfaction. We discuss some implications of the findings, including the importance of applying a multidimensional approach to studying employee well-being and potential opportunities for organizations to support the well-being of their employees.